ESTUDIO DEL EFECTO DE DOS BIOCONSERVANTES: ACEITE ESENCIAL DE CULANTRO SILVESTRE (Eryngium foetidum) Y LA BACTERIA ÁCIDO-LÁCTICA (Lactobacillus plantarum) MEDIANTE LA TÉCNICA DE ENCAPSULAMIENTO, EN LA CONSERVACIÓN DE PRODUCTOS CÁRNICOS AHUMADOS (CHULETA DE CERDO (Sus scrofa)) - Guadamud Briones, Yelena Jahaira (2023)
The main objective of this research is to study the effect of the application of two biopreservatives: the essential oil of wild coriander (Eryngium foetidum) and the lactic acid bacteria (Lactobacillus plantarum) in smoked pork chops. For which a factorial design AxBxC was applied where factor A: Types of biopreservatives (essential oil of wild coriander (Eryngium foetidum) and lactic acid bacteria (Lactobacillus plantarum)) factor B: Types of concentrations (1%, 2% and 3%) factor C: application methods (spray method and encapsulation method) by means of the statistical method ANOVA and the significance test of TUKEY (P<0.05) by means of the STHAGRAPHIS and STATISTICA programs, where the best treatments were chosen with a margin of error of 5%.